Peripartum hysterectomy in a tertiary care hospital: Epidemiology and outcomesImproving outcomes for peripartum hysterectomy: Still a long way to go! - Bharti Sharma; Pooja Sikka; Vanita Jain; Kajal Jain; Rashmi Bagga; Vanita Suri (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Peripartum hysterectomy is associated with significant maternal morbidity and mortality. We reviewed all peripartum hysterectomies at our institute over a 1-year period. The aim of this study was to determine the incidence, surgery and anesthesia-related issues of peripartum hysterectomies and to compare outcomes of emergency and electively planned peripartum hysterectomies. Material and Methods: This was a retrospective analysis of records of women who underwent emergency or elective peripartum hysterectomy in a tertiary care hospital. The study included all women who underwent peripartum hysterectomy in a teaching hospital and referral institute in North India over a span of 1 year (April 1, 2014, to March 31, 2015). Association of variables was based on Chi-square test, Fisher's exact test, and comparison on "t" statistics (normal distribution) and Mann-Whitney (nonnormal distribution). Results: Forty women underwent peripartum hysterectomy during the study period. The incidence was 6.9/1000 deliveries. In 16 (40%) cases, peripartum hysterectomy was planned electively while emergency hysterectomy was done in 24 (60%) cases. Main indications of peripartum hysterectomies were placenta accreta (60%), atonic postpartum hemorrhage (PPH) (27.5%), and uterine rupture (7.5%). Intensive care management was required in 35% women postoperatively. The common maternal complications were febrile morbidity, bladder injury, disseminated intravascular coagulation, and wound infection. There were 4 maternal deaths following emergency peripartum hysterectomy done for atonic PPH whereas no mortality occurred in elective hysterectomy group. Conclusions: The most common indication for peripartum hysterectomy was placenta accrete. Electively planned peripartum hysterectomies with a multidisciplinary team approach had better outcomes and no mortality as compared to emergency peripartum hysterectomies.